obstacles to applying electronic management in the College of Arts - Sebha University (Journal of Human Sciences, 2025)
This research paper seeks to identify the obstacles that prevent the application of electronic management from the point of view of employees in the Faculty of Arts - Sabha University And to identify the obstacles that hinder the application of electronic management systems in the university in its various types of  administrative , organizational , technical , human and financial . The research aims to identify the most important obstacles that hinder the application of electronic management systems in universities, and the sample consists of 45 male and female employees , The researcher used the questionnaire to collect information and data in several axes , which are organizational , technical, human and financial obstacles , She used the descriptive analytical approach and used statistical methods such as percentage , arithmetic mean and coefficient (alpha). The researcher reached the following most important results : The arithmetic averages of the obstacles to the application of electronic management in the Faculty of Arts from the point of view of employees came at a medium level within the axis of organizational , technical and human information , while in the axis of financial information it came at a low level , There are no statistically significant differences in the obstacles to the application of electronic management in the Faculty of Arts from the point of view of employees according to the gender variable , There are no statistically significant differences in the obstacles to the application of electronic management in the Faculty of Arts from the point of view of employees according to the age variable , There are no statistically significant differences in the obstacles to the application of electronic management in the Faculty of Arts from the point of view of employees according to the variable of years of service .